Formal Mentorship and Leadership Training Contributes to the Development and Expertise of Graduate Students as Teachers, Scientists, and Engineers - Parker J. Esswein; Clare B. Cook; Lailah Ligons; Kiarra Richardson; Marc A. Sommer; Cameron M. Kim (Biomedical Engineering Education, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

A systems modelling approach to predict biological responses to extreme heat - Daniel W.A. Noble; Margaret M. Mayfield; Ary A. Hoffmann; Zhong-Hua Chen; Steven J. Lade; Xuemei Bai; Danielle A. Way; Belinda E. Medlyn; Owen K. Atkin; Adrienne B. Nicotra; James M. Cook; Brajesh K. Singh; et al. (Trends in Ecology & Evolution, 2026)

Morphological and heat-tolerance traits are associated with progression and impact of, but not vulnerability to, tree decline - Sabina M. Aitken; Pieter A. Arnold; Matthew T. Brookhouse; Alicia M. Cook; Lisa M. Danzey; Rosalie J. Harris; Andy Leigh; Adrienne B. Nicotra (Forest Ecology and Management, 2026)

Cognition as a Conservation Tool: A Case Study of Florida Manatees and Boat Strikes - Gordon B. Bauer; Charles J. Deutsch; Roger L. Reep; Wendi Fellner; Tabitha Gunnars; Peter F. Cook; Heidi E. Harley; Athena M. Rycyk (Marine Mammal Science, 2026)
Boat strikes injure and kill large numbers of Florida manatees ( Trichechus manatus latirostris ) each year. Management actions taken to mitigate this threat can be potentially enhanced by consideration of manatee cognitive processes. The role of cognition in marine mammal conservation has received little consideration in the literature. Here, we integrate discoveries from laboratory research on auditory sensory processes and perception with findings from field studies of how manatees respond to motorized vessels and the effect of the ambient soundscape on response times to boat noise. We incorporate that information into recommendations for manatee management to further reduce the risk of collisions. We also suggest lines of research to investigate other relevant cognitive issues—including attention, learning, memory, and decision‐making—to improve conservation efforts and understanding of manatee behavior.

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Exploring Marine Mammal Cognition as a Conservation Tool - Gordon B. Bauer; Peter F. Cook; Heidi E. Harley; Jason Bruck; Mel Cosentino; Charles J. Deutsch; Nicola Erdsack; Wendi Fellner; Tabitha Gunnars; Heather Manitzas Hill; Sonia V. Kumar; Malin K. Lilley; et al. (Marine Mammal Science, 2026)
Cognition is an animal's real‐time adaptation system for responding to change. Rapid environmental change, often anthropogenic, is expanding the range and severity of challenges confronting wild animals. Effective conservation requires a multifaceted approach that includes animals' capacities. Large‐brained, long‐lived animals such as marine mammals often have extensive capability to adaptively modify their behavior due to their cognition, which comprises the mechanisms of information acquisition, processing, and flexible action. Consequently, current behavior need not be a final predictor of future behavior for these animals. This flexibility provides an underutilized and under examined point of leverage for humans interested in improving life outcomes for wild animals. In this team‐written, interdisciplinary paper, we argue that application of cognitive approaches may facilitate many conservation efforts directed toward marine mammals. Starting with a workshop on this topic at the 24th Biennial Conference on the Biology of Marine Mammals, scientists representing a wide range of disciplinary expertise addressed eight different conservation concerns for six marine mammal species and provided potential cognitive explanations of and interventions aimed at related behavior. Our treatment highlights the value of integrated laboratory and field research, and the importance of tight lines of communication between scientists and conservation managers.

A decision support tool for rubble stabilization on coral reefs - Shu Kiu Leung; Tania M. Kenyon; Laurie J. Raymundo; Helen E. Fox; Nathan Cook; Kailash Cook; Alasdair J. Edwards; Eric E. Fisher; Arnaud J.T. Brival; Freda E. Nicholson; Robin W.L. Philippo; Andrew C.F. Taylor; et al. (Journal of Environmental Management, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Ecosystem-wide PFAS characterization and environmental behavior at a heavily contaminated desert oasis in the southwestern U.S. - Jean-Luc E. Cartron; Chauncey R. Gadek; Jonathan L. Dunnum; Christopher C. Witt; Mariel L. Campbell; Samuel J. Romero; Andrew B. Johnson; Julie Kutz; Christopher Wolf; Sarah J. Choyke; Joseph A. Cook (Environmental Research, 2025)

Native Australian seedlings exhibit novel strategies to acclimate to repeated heatwave events - Philippa R. Alvarez; Rosalie J. Harris; Alicia M. Cook; Verónica F. Briceño; Adrienne B. Nicotra; Andrea Leigh (Oecologia, 2025)
Heatwaves are becoming more intense and frequent. Plant photosystem thermal thresholds can vary with species, but also shift in response to environmental triggers. Both upper and lower thresholds can acclimate to repeated heatwaves through ecological stress memory, where prior exposure primes them for subsequent events. The extent to which acclimation to repeated heat stress events varies among environmental origin and/or species is unknown. Different acclimation strategies might reflect biome of origin, or may be species-specific. For 12 species from two contrasting biomes—extreme desert and benign coastal temperate—we investigated responses to two simulated heatwaves, via shifts in upper and lower critical temperatures of photosystem II, and the difference between these thresholds, thermal tolerance breadth (TTB). Biome of origin had no effect on thermal tolerance. Observed differences among species following heat events suggested two possible acclimatory strategies. In some cases, species increased thermal thresholds during the first heatwave, but at the cost of reduced thermal tolerance during the second heatwave, a sprinter strategy. Other species acclimated to the first heatwave and further increased thermal tolerance to a second heatwave, indicative of ecological stress memory, a marathoner strategy. Synthesis: these among-species responses to heatwaves could suggest distinct vulnerabilities and resilience to repeat heat stress events, with some species having limited capacity to tolerate consecutive heatwaves, possibly as the cost of acclimation is too great, with other species having the advantage of increased tolerance via stress memory, helping them survive future stress, at least in the short-term.

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Past and present bacterial communities in deglaciating northern latitude catchments reveal varied soil carbon sequestration potential - Saule Akhmetkaliyeva; Andrew P. Dean; Leon J. Clarke; Simon J. Cook; Sharon Ruiz Lopez; Robert B. Sparkes (Science of The Total Environment, 2025)

Reversal of practical resistance in fall armyworm to Cry1F maize: a case report on the resistance to susceptibility in Bt crops from the southeastern USA - Tiago Silva; Gregory A. Sword; Andie Miller; Jawwad A. Qureshi; Graham P. Head; Dawson D. Kerns; Juan Luis Jurat-Fuentes; James Villegas; Tyler B. Towles; Xinzhi Ni; Francis P. F. Reay-Jones; Daniel Carrillo; et al. (Journal of Pest Science, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Operational lessons learned from simulating an elimination response to a transboundary animal disease in wild animals - K. Chalkowski; K.M. Pepin; M.J. Lavelle; R.S. Miller; J. Fischer; V.R. Brown; M. Glow; B. Smith; S. Cook; K. Kohen; S. Sherburne; H. Smith; et al. (Preventive Veterinary Medicine, 2025)

Dietary Fiber Intake and Risk of Advanced and Aggressive Forms of Prostate Cancer: A Pooled Analysis of 15 Prospective Cohort Studies - Elkhansa Sidahmed; Stephen J. Freedland; Molin Wang; Kana Wu; Demetrius Albanes; Matt Barnett; Piet A. van den Brandt; Michael B. Cook; Graham G. Giles; Edward Giovannucci; Christopher A. Haiman; Susanna C. Larsson; et al. (Journal of the Academy of Nutrition and Dietetics, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Avoidance and attraction responses of kittiwakes to three offshore wind farms in the North Sea - Christopher J. Pollock; Daniel T. Johnston; Philipp H. Boersch-Supan; Chris B. Thaxter; Elizabeth M. Humphreys; Nina J. O’Hanlon; Gary D. Clewley; Ewan D. Weston; Judy Shamoun-Baranes; Aonghais S. C. P. Cook (Marine Biology, 2024)
Seabird collision risk is a key concern in relation to the environmental impacts associated with offshore wind farms (OWFs). Understanding how species respond both to the wind farm itself, and individual turbines within the wind farm, is key to enabling better quantification and management of collision risk. Collision risk is of particular concern for the black-legged kittiwake, Rissa tridactyla , where modelling predicts unsustainable population level impacts. In this study 20 adult breeding kittiwakes, were tracked with GPS from Whinnyfold, Scotland (57°23′07″N, 001°52′11″W) during the breeding season in 2021. An Avoidance-Attraction Index (AAI) was estimated at several bands within macro- and meso-scales (0–4 km from outer boundary and 0–400 m from turbines, respectively), and the Avoidance Rate (AR; used in environmental impact assessments) at macro-scale to estimate avoidance behaviour to three operational OWFs within their foraging range. One offshore wind farm and its buffer zone (0–4 km from outer boundary) was visited more frequently by the majority of tracked individuals (19/20 birds), despite being twice as far as the closest OWF (17.3 and 31.9 km respectively), whilst 10 or less individuals used the remaining two OWFs. At the most frequented OWF we found macro-scale attraction to the closest band (0–1 km) trending towards avoidance in the furthest band (3–4 km). At the meso-scale we found avoidance of areas below the rotor height range (RHR, a.k.a. rotor swept area/zone) up to 120 m from individual turbines, which decreased to 60 m when within the RHR. Our results indicate that kittiwakes may be slightly attracted to the area around OWFs or aggregate here due to displacement but avoid individual turbines. Increased productivity in the OWF area may potentially be drawing birds into the general area, with aversion to individual turbines being responsible for meso-scale observations.

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Influence of wind on kittiwake Rissa tridactyla flight and offshore wind turbine collision risk - Jacob G. Davies; Philipp H. Boersch-Supan; Gary D. Clewley; Elizabeth M. Humphreys; Nina J. O’Hanlon; Judy Shamoun-Baranes; Chris B. Thaxter; Ewan Weston; Aonghais S. C. P. Cook (Marine Biology, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Investigating the physiological ecology of mesopelagic zooplankton in the Scotia sea (Southern ocean) using lipid and stable isotope signatures - Eloïse Linda-Roselyne Savineau; Kathryn B. Cook; Sabena J. Blackbird; Gabriele Stowasser; Konstadinos Kiriakoulakis; Calum Preece; Sophie Fielding; Anna C. Belcher; George A. Wolff; Geraint A. Tarling; Daniel J. Mayor (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

Extraordinary levels of per- and polyfluoroalkyl substances (PFAS) in vertebrate animals at a New Mexico desert oasis: Multiple pathways for wildlife and human exposure - Christopher C. Witt; Chauncey R. Gadek; Jean-Luc E. Cartron; Michael J. Andersen; Mariel L. Campbell; Marialejandra Castro-Farías; Ethan F. Gyllenhaal; Andrew B. Johnson; Jason L. Malaney; Kyana N. Montoya; Andrew Patterson; Nicholas T. Vinciguerra; et al. (Environmental Research, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

The influence of the toxin-producing dinoflagellate, Alexandrium catenella, on feeding, reproduction and toxin retention in Calanus helgolandicus - Ali H. Abdulhussain; Kathryn B. Cook; Eileen Bresnan; Jean-Pierre Lacaze; Daniel J. Mayor (Harmful Algae, 2024)

Behavioural responses of Sandwich terns following the construction of offshore wind farms - Chris B. Thaxter; Ros M. W. Green; Mark P. Collier; Rachel C. Taylor; Robert P. Middelveld; Emily S. Scragg; Lucy J. Wright; Aonghais S. C. P. Cook; Ruben C. Fijn (Marine Biology, 2024)

Short communication: Circadian variations and day-to-day variability of clinical signs used for the early diagnosis of pneumonia within and between calves - T. Lowie; J. Vandewalle; G. Hanley-Cook; B. Pardon; J. Bokma (Research in Veterinary Science, 2024)

Corrigendum to “Evaluation of the impact of aquatic-animal excretion on nutrient recycling and retention in stormwater treatment wetlands” [Ecological Engineering 197 (2023) 1–20/107104] - Mark B. Barton; Janelle A. Goeke; Nathan J. Dorn; Mark I. Cook; Susan Newman; Joel C. Trexler (Ecological Engineering, 2023)

Evaluation of the impact of aquatic-animal excretion on nutrient recycling and retention in stormwater treatment wetlands - Mark B. Barton; Janelle A. Goeke; Nathan J. Dorn; Mark I. Cook; Susan Newman; Joel C. Trexler (Ecological Engineering, 2023)

Derivation of Naïve Human Embryonic Stem Cells Using a CHK1 Inhibitor - Carol B. Ware; Erica C. Jonlin; Donovan J. Anderson; Christopher Cavanaugh; Jennifer Hesson; Sonia Sidhu; Savannah Cook; Guillermo Villagomez-Olea; Marshall S. Horwitz; Yuliang Wang; Julie Mathieu (Stem Cell Reviews and Reports, 2023)
Embryonic development is a continuum in vivo . Transcriptional analysis can separate established human embryonic stem cells (hESC) into at least four distinct developmental pluripotent stages, two naïve and two primed, early and late relative to the intact epiblast. In this study we primarily show that exposure of frozen human blastocysts to an inhibitor of checkpoint kinase 1 (CHK1) upon thaw greatly enhances establishment of karyotypically normal late naïve hESC cultures. These late naïve cells are plastic and can be toggled back to early naïve and forward to early primed pluripotent stages. The early primed cells are transcriptionally equivalent to the post inner cell mass intermediate (PICMI) stage seen one day following transfer of human blastocysts into in vitro culture and are stable at an earlier stage than conventional primed hESC. Graphical Abstract

Drought conditioning of rhizosphere microbiome influences maize water use traits - Kelsey R. Carter; Abigael C. Nachtsheim; L. Turin Dickman; Eric R. Moore; Sangeeta Negi; John P. Heneghan; Anthony J. Sabella; Christina R. Steadman; Michaeline B. N. Albright; Christine M. Anderson-Cook; Louise H. Comas; Rose J. Harris; et al. (Plant and Soil, 2023)
Background and Aims Beneficial plant–microbe interactions can improve plant performance under drought; however, we know less about how drought-induced shifts in microbial communities affect plant traits. Methods We cultivated Zea mays in fritted clay with soil microbiomes originating from contrasting environments (agriculture or forest) under two irrigation treatments (well-watered or water limited). Using this design, we investigated whether water conditioning was carried forward through the microbiome to affect a subsequent plant cohort that was subjected to either a well-watered or water limited treatment. Results Regardless of the microbiome-origin, plants inoculated with a microbiome from a water limited legacy had traits that allowed them to avoid stress but conserve water. They produced longer roots to explore soil, generated greater soil dissolved organic carbon, potentially stimulating the microbiome, and slower soil water content loss during drought. A well-watered legacy resulted in plants that delayed permanent stomatal closure and higher photosynthetic nitrogen use efficiency. In plants with a forest-originated microbiome, a well-watered legacy and water treatment also resulted in higher rates of photosynthesis and stomatal conductance. Conclusion These results demonstrate that soil microbiomes can be developed to influence plant drought performance, impacting crop resilience, using short-term microbial conditioning.

Seasonal Rainfall, Shrub Cover and Soil Properties Drive Production of Winter Annuals in the Northern Sonoran Desert - Julea A. Shaw; Scott L. Collins; Timothy J. Ohlert; Hannah Heavenrich; Elizabeth Cook; Megan M. Wheeler; Nancy B. Grimm; Sharon J. Hall (Ecosystems, 2023)

Development and Validation of an Abbreviated Child and Adult Food Security Scale for Use in Clinical and Research Settings in the United States - Ana Poblacion; Stephanie Ettinger de Cuba; Deborah A. Frank; Georgiana Esteves; Lindsey J. Rateau; Timothy C. Heeren; Sharon Coleman; Maureen M. Black; Diana B. Cutts; Félice Lê-Scherban; Eduardo R. Ochoa; Megan Sandel; et al. (Journal of the Academy of Nutrition and Dietetics, 2023)

Using in-situ strain measurements to evaluate the accuracy of stress estimation procedures from fracture injection/shut-in tests - Yves Guglielmi; Mark McClure; Jeffrey Burghardt; Joseph P. Morris; Thomas Doe; Pengcheng Fu; Hunter Knox; Vince Vermeul; Tim Kneafsey; J. Ajo-Franklin; T. Baumgartner; K. Beckers; et al. (International Journal of Rock Mechanics and Mining Sciences, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Carbon budgets of Scotia Sea mesopelagic zooplankton and micronekton communities during austral spring - Kathryn B. Cook; Anna Belcher; Daniel Bondyale Juez; Gabriele Stowasser; Sophie Fielding; Ryan A. Saunders; Mohamed A. Elsafi; George A. Wolff; Sabena J. Blackbird; Geraint A. Tarling; Daniel J. Mayor (Deep Sea Research Part II: Topical Studies in Oceanography, 2023)

Associations of urinary metabolite concentrations of phthalates and phthalate replacements with body composition from mid-childhood to early adolescence - Lisa B. Rokoff; Shravanthi M. Seshasayee; Jenny L. Carwile; Sheryl L. Rifas-Shiman; Julianne Cook Botelho; Catherine M. Gordon; Russ Hauser; Tamarra James-Todd; Jessica G. Young; Clifford J. Rosen; Antonia M. Calafat; Emily Oken; et al. (Environmental Research, 2023)

Total thermal neutron cross section measurements of hydrogen dense polymers from 0.0005–20 eV - D. Fritz; Y. Danon; K. Ramic; C.W. Chapman; J.M. Brown; G. Arbanas; M. Rapp; T.H. Trumbull; M. Zerkle; J. Holmes; P. Brain; A. Ney; et al. (Annals of Nuclear Energy, 2023)

Overview of global Gracilaria production, the role of biosecurity policies and regulations in the sustainable development of this industry - Vaibhav A. Mantri; Cicilia S. B. Kambey; Elizabeth J. Cottier‐Cook; Sara Usandizaga; Alejandro H. Buschmann; Ik Kyo Chung; Tao Liu; Calvyn F. A. Sondak; Zizhong Qi; Phaik Eem Lim; Nguyen Van Nguyen (Reviews in Aquaculture, 2023)
Gracilaria aquaculture is one of the fastest‐growing sectors, contributing to 10.5% of the global seaweed feed‐stock supply chain in 2019. It predominantly caters to food‐grade agar, animal feed and non‐food sector applications viz. biotechnology, biomedical and pharmaceuticals. It has witnessed a rapid expansion triggered by increased demand due to commodity trade. Biosecurity‐related issues are the key factors constraining its expansion, but are seldom addressed. The global gracilarioids aquaculture is dominated by China and other Asian countries, namely the Republic of Korea, Indonesia, the Philippines and Vietnam. This paper provides an assessment of their national biosecurity capacity, including current risk management strategies, policies and the implementation of existing regulations. It also highlights specific gaps in national policies and regulations, which can be addressed to improve their health management systems. Biosecurity management strategies, such as the provision of clear regulatory guidance, mechanisms for notifying disease and pest outbreaks, movement of live seaweed, risk assessment, stakeholder incentivisation and certification are recommended. Further, insights into the impending biosecurity measures to the emerging countries in this domain namely India and Malaysia are discussed. We suggest, implementing a uniform format of global integrated biosecurity measures across the Gracilaria aquaculture industry, but this requires organisational, operational and procedural changes, coupled with a cross‐sectoral application of risk analysis protocols. Despite one of the important seaweed aquaculture taxa, an overview of Gracilaria production, the role of biosecurity policy and regulation in the sustainable development of this industry was still lacking, this is the first global effort in this direction.

Total thermal neutron cross section measurements of yttrium hydride from 0.0005 - 3 eV - D. Fritz; Y. Danon; M. Rapp; T.H. Trumbull; M. Zerkle; J. Holmes; C.W. Chapman; G. Arbanas; J.M. Brown; K. Ramic; X. Hu; S. Singh; et al. (Annals of Nuclear Energy, 2023)

Effect of biosecurity practices and diseases on growth and carrageenan properties of Kappaphycus alvarezii and Eucheuma denticulatum cultivated in Zanzibar, Tanzania - Msafiri A. Ndawala; Flower E. Msuya; Jennefe P. Cabarubias; Cicilia S. B. Kambey; Amelia S. Buriyo; Esther F. Mvungi; Elizabeth J. Cottier-Cook (Journal of Applied Phycology, 2022)

Grazing, egg production and carbon budgets for Calanus finmarchicus across the Fram Strait - Holly E. Jenkins; Florence Atherden; Kathryn B. Cook; Thomas R. Anderson; Barry Thornton; Elaine Mitchell; Elodie Jacob; Daniel J. Mayor (Frontiers in Marine Science, 2022)
Calanoid copepods comprise around 90% of Arctic zooplankton biomass and are fundamental to the ecological and biogeochemical functioning of high-latitude pelagic ecosystems. They accumulate lipid reserves during the productive months and represent an energy-rich food source for higher trophic levels. Rapidly changing climate in the Arctic may alter the quantity and composition of the food environment for one of the key copepod species, Calanus finmarchicus , with as yet unquantified effects on its production. Here we present rates of feeding and egg production in female C. finmarchicus exposed to the range of feeding conditions encountered across the Fram Strait in May/June 2018. Carbon (C) budgets were constructed and used to examine the relationship between feeding and growth (= egg production) in these animals. C-specific ingestion rates (mean ± standard deviation) were highly variable, ranging from 0.015 ± 0.004 to 0.645 ± 0.017 day -1 (mean = 0.295 ± 0.223 day -1 ), and were positively correlated with food availability. C-specific egg production rates ranged from 0.00 to 0.049 day -1 (mean = 0.012 ± 0.011) and were not correlated with either food availability or ingestion rate. Calculated gross growth efficiencies (GGE: growth/ingestion) were low, 0.12 ± 0.13 (range = 0.01 to 0.39). The assembled C budgets indicate that the average fraction of ingested food that was surplus to the requirements for egg production, respiration and losses to faecal pellets was 0.17 ± 0.42. We suggest that this excess occurred, at least in part, because many of the incubated females were still undergoing the energetically (C-) expensive process of gonad maturation at the time of sampling, an assertion that is supported by the relatively high C:N (nitrogen) ratios of the incubated females, the typically low egg production rates, and gonad maturation status. Ontogenetic development may thus explain the large variability seen in the relationship between egg production and ingestion. The apparently excessive ingestion rates may additionally indicate that recently moulted females must acquire additional N via ingestion to complete the maturation process and begin spawning. Our results highlight the need for improved fundamental understanding of the physiology of high-latitude copepods and its response to environmental change.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Red Pigmentation Can Be Used to Reliably Distinguish Between Live Calanus finmarchicus and Calanus glacialis Females in the Fram Strait - Penelope K. Lindeque; Isabelle Hann; Helen E. Parry; Kathryn B. Cook; Anthony J. W. Lindley; Daniel J. Mayor (Frontiers in Marine Science, 2022)
Copepods from the genus Calanus provide an important lipid-rich food source in the Arctic marine foodweb. Despite extensive research on Calanus finmarchicus and Calanus glacialis , accurately identifying adults to species level remains challenging due to similar morphologies. Although these species co-occur in many regions, the distribution of C. finmarchicus and C. glacialis correspond to Atlantic and Arctic water masses respectively and are frequently used as climate indicators. Correct identification is therefore vital for understanding the phenotypic plasticity of these species and the impacts climate change will have on Calanus- dominated marine ecosystems. In this study, prosome length and percentage of red pigmentation (redness) of genital somites, the antennae, and throughout the whole body were determined for 139 females of C. finmarchicus and C. glacialis from the Fram Strait. Molecular analysis of a 16S rDNA barcode confirmed that the best morphological features for resolving the identity of these two species were the redness of the antennae and the redness of the genital somites. Overall accuracy of using antennae redness and genital somite redness to discriminate between the two species were the same, yet each of these explanatory variables had different specificity; C. finmarchicus were more accurately identified by the absence of redness in the genital somites, whereas C. glacialis were more accurately identified using antennae redness. Given the ecological importance of these congeners, these findings contribute to a better understanding of the reliability of using morphological characteristics to identify Calanus to species level, especially when sorting live specimens for climate-related ecological experiments.

Biomass Turnover Rates in Metabolically Active and Inactive Marine Calanoid Copepods - Daniel J. Mayor; Kathryn B. Cook; Barry Thornton; Florence Atherden; Geraint A. Tarling; Thomas R. Anderson (Frontiers in Marine Science, 2022)
Lipid-storing copepods are fundamental to the functioning of marine ecosystems, transferring energy from primary producers to higher trophic levels and sequestering atmospheric carbon (C) in the deep ocean. Quantifying trophic transfer and biogeochemical cycling by copepods requires improved understanding of copepod metabolic rates in both surface waters and during lipid-fueled metabolism over winter. Here we present new biomass turnover rates of C and nitrogen (N) in Calanoides acutus , Calanoides natalis , Calanus glacialis and Calanus hyperboreus alongside published data for Calanus finmarchicus and Calanus pacificus . Turnover rates in metabolically active animals, normalised to 10°C, ranged between 0.007 – 0.105 d -1 and 0.004 – 0.065 d -1 for C and N, respectively. Turnover rates of C were typically faster than those for N, supporting the understanding that non-protein C, e.g. lipid, is catabolised faster than protein. Re-analysis of published data indicates that inactive, overwintering C. finmarchicus turn over wax ester lipids at a rate of 0.0016 d -1 . These and other basal rate data will facilitate the mechanistic representation of copepod physiology in global biogeochemical models, thereby reducing uncertainties in our predictions of future ocean ecosystem functioning and C sequestration.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

The Open-Ocean Gulf of Mexico After Deepwater Horizon: Synthesis of a Decade of Research - Tracey T. Sutton; Rosanna J. Milligan; Kendra Daly; Kevin M. Boswell; April B. Cook; Maëlle Cornic; Tamara Frank; Kaitlin Frasier; Daniel Hahn; Frank Hernandez; John Hildebrand; Chuanmin Hu; et al. (Frontiers in Marine Science, 2022)
The scale of the Deepwater Horizon disaster was and is unprecedented: geographic extent, pollutant amount, countermeasure scope, and of most relevance to this Research Topic issue, range of ecotypes affected. These ecotypes include coastal/nearshore, continental shelf, deep benthic, and open-ocean domains, the last of which is the subject of this synthesis. The open-ocean ecotype comprises ~90% of the volume of the Gulf of Mexico. The exact percentage of this ecotype contaminated with toxins is unknown due to its three-dimensional nature and dynamics, but estimates suggest that the footprint encompassed most of its eastern half. Further, interactions between the water column and the deep benthos may be persistent, making this synthesis one of time (a decade) rather than event conclusion. Here we examine key elements of the open-ocean ecosystem, with emphasis on vulnerability and resilience. Of paramount importance relative to the Gulf nearshore and shelf ecotypes, pre-disaster baseline data were lacking for most of the fauna. In such cases, inferences were drawn from post-disaster assessments. Both phytoplankton and mesozooplankton vulnerabilities were quite high, but resilience appeared equally so. The phytoplankton situation was a bit more complex in that toxin-imposed reductions may have been offset by nutrient injection via high freshwater discharge in 2010. Intermediate trophic levels exhibited population-level depressions, ostensibly due to high vulnerability and low resilience. Apex predator impacts were variable. Certain large epipelagic fishes may have avoided the highest concentrations of hydrocarbons/dispersant, and thus larval abundances returned to pre-disaster levels of variability and abundance within a few years after a steep initial decline. Oceanic cetaceans, particularly shallow-diving stenellid dolphins, did not appear to avoid oiled waters and exhibited strong declines in the northern Gulf. Given that population declines of many open-ocean taxa appear to be ongoing a decade later, we conclude that this largest of Gulf ecosystem components, like its deep-benthic counterpart, is as fragile as it is voluminous. This is particularly concerning given the rapid, and likely irreversible, shift to deeper waters by the US and Mexican oil industries in concert with the higher likelihood of accidents with increasing platform depth.

Expert range maps of global mammal distributions harmonised to three taxonomic authorities - Charles J. Marsh; Yanina V. Sica; Connor J. Burgin; Wendy A. Dorman; Robert C. Anderson; Isabel del Toro Mijares; Jessica G. Vigneron; Vijay Barve; Victoria L. Dombrowik; Michelle Duong; Robert Guralnick; Julie A. Hart; et al. (Journal of Biogeography, 2022)
Aim Comprehensive, global information on species' occurrences is an essential biodiversity variable and central to a range of applications in ecology, evolution, biogeography and conservation. Expert range maps often represent a species' only available distributional information and play an increasing role in conservation assessments and macroecology. We provide global range maps for the native ranges of all extant mammal species harmonised to the taxonomy of the Mammal Diversity Database (MDD) mobilised from two sources, the Handbook of the Mammals of the World (HMW) and the Illustrated Checklist of the Mammals of the World (CMW). Location Global. Taxon All extant mammal species. Methods Range maps were digitally interpreted, georeferenced, error‐checked and subsequently taxonomically aligned between the HMW (6253 species), the CMW (6431 species) and the MDD taxonomies (6362 species). Results Range maps can be evaluated and visualised in an online map browser at Map of Life ( mol.org ) and accessed for individual or batch download for non‐commercial use. Main conclusion Expert maps of species' global distributions are limited in their spatial detail and temporal specificity, but form a useful basis for broad‐scale characterizations and model‐based integration with other data. We provide georeferenced range maps for the native ranges of all extant mammal species as shapefiles, with species‐level metadata and source information packaged together in geodatabase format. Across the three taxonomic sources our maps entail, there are 1784 taxonomic name differences compared to the maps currently available on the IUCN Red List website. The expert maps provided here are harmonised to the MDD taxonomic authority and linked to a community of online tools that will enable transparent future updates and version control.

Training needs assessment of veterinary practitioners in Ethiopia - Ruth Alafiatayo; Erika Galipo; Abel B. Ekiri; Mariana Dineva; Isabella Endacott; Tewodros Tesfaye; Gewado Gellebo; Fasil Awol; Erik Mijten; Gabriel Varga; Alasdair J. C. Cook (Tropical Animal Health and Production, 2022)
Pastoral and agro-pastoral farming are extensively practised in Ethiopia, and the main livestock kept are cattle, goats, sheep, poultry, and camels. The livestock sector is faced with complex challenges including limited availability of well-trained and skilled animal health professionals. The objective of this study was to identify and prioritise areas for training with the goal of providing evidence to guide strategies to improve the skills, delivery, and governance of veterinary services across Ethiopia. A cross-sectional survey was developed and administered electronically to veterinary professionals in Ethiopia using the Qualtrics platform. Data were collected on select parameters including demographics, diseases of economic significance, diagnosis, disease prevention, biosecurity, disease control, treatment, epidemiology, One Health, disease reporting, and the participants’ opinions about training. The survey data was downloaded in Microsoft Excel and descriptive statistics performed. A total of 234 veterinary professionals completed the survey. Most participants were male (89.7%) and aged between 26 and 35 years (81.2%). Of the total respondents, 56.4% worked in government and 8.5% in private practice. Most participants perceived training on laboratory diagnostic testing, disease prevention, antimicrobial resistance, antibiotic sensitivity testing, basic epidemiology, and clinical procedures, as most beneficial. In addition, most respondents would like to receive training on diseases affecting cattle, poultry, and small ruminants. The findings from this study provide baseline information on priority training areas for veterinary professionals and could potentially contribute to national efforts to develop and implement a continuing professional development programme in the veterinary domain, in view of improving veterinary service delivery.

Can a key boreal Calanus copepod species now complete its life-cycle in the Arctic? Evidence and implications for Arctic food-webs - Geraint A. Tarling; Jennifer J. Freer; Neil S. Banas; Anna Belcher; Mayleen Blackwell; Claudia Castellani; Kathryn B. Cook; Finlo R. Cottier; Malin Daase; Magnus L. Johnson; Kim S. Last; Penelope K. Lindeque; et al. (Ambio, 2022)
The changing Arctic environment is affecting zooplankton that support its abundant wildlife. We examined how these changes are influencing a key zooplankton species, Calanus finmarchicus , principally found in the North Atlantic but expatriated to the Arctic. Close to the ice-edge in the Fram Strait, we identified areas that, since the 1980s, are increasingly favourable to C. finmarchicus . Field-sampling revealed part of the population there to be capable of amassing enough reserves to overwinter. Early developmental stages were also present in early summer, suggesting successful local recruitment. This extension to suitable C. finmarchicus habitat is most likely facilitated by the long-term retreat of the ice-edge, allowing phytoplankton to bloom earlier and for longer and through higher temperatures increasing copepod developmental rates. The increased capacity for this species to complete its life-cycle and prosper in the Fram Strait can change community structure, with large consequences to regional food-webs.

Geographic variation of mercury in breeding tidal marsh sparrows of the northeastern United States - Christopher J. Sayers; Mackenzie R. Roeder; Lindsay M. Forrette; Daniel Roche; Gaetan L. B. Dupont; Sam E. Apgar; Alison R. Kocek; Alexandra M. Cook; W. Gregory Shriver; Chris S. Elphick; Brian Olsen; David N. Bonter (Ecotoxicology, 2021)

The Toxicology Investigators Consortium 2020 Annual Report - Meghan B. Spyres; Kim Aldy; Lynn A Farrugia; A. Min Kang; Jennifer S. Love; Sharan L. Campleman; Shao Li; Alexandra Amaducci; Evan Schwarz; Paul M. Wax; Jeffery Brent; J. Acciani; et al. (Journal of Medical Toxicology, 2021)

Seaweed aquaculture: a preliminary assessment of biosecurity measures for controlling the ice-ice syndrome and pest outbreaks of a Kappaphycus farm - Cicilia S. B. Kambey; Iona Campbell; Elizabeth J. Cottier-Cook; Adibi R. M. Nor; Azhar Kassim; Ahemad Sade; Phaik E. Lim (Journal of Applied Phycology, 2021)
The application of biosecurity in seaweed aquaculture plays an important role in reducing the impact of disease and pest outbreaks. The continuous occurrence of seaweed pests including the macroalgal epiphytes, epi-endophytic filamentous algae and biofilms on Kappaphycus farms may also potentially induce further incidences of the ice-ice syndrome. In this study, on-farm biosecurity management measures were tested on the commercially grown seaweeds Kappaphycus malesianus and Kappaphycus alvarezii during peak ice-ice season at Gallam-Gallam Village, Sabah, Malaysia. The investigation was focused on preventative control measures including the early detection of the ice-ice syndrome and pests through propagule health checks, regular cleaning of the crop thallus and associated long-line ropes and monitoring of the environment. Farm procedures and practices were also assessed in terms of their biosecurity ‘risk’ using the hazard analysis and critical control point (HCCAP) approach. Observations were replicated in two different farm management systems; one system adopted routine biosecurity measures and the other had no biosecurity measures. The results showed that the ice-ice syndrome and pest outbreak was significantly decreased by 60–75% for K. malesianus and 29–71% for K. alvarezii at the farm which adopted the routine biosecurity measures compared with the no biosecurity treatment. The biosecurity measures also significantly improved growth rate and seaweed quality. The infection levels of the epi-endophyte Melanothamnus sp. contributed to the ice-ice syndrome in K. malesianus , whilst the epiphyte coverage was correlated to the ice-ice incidence in K. alvarezii . This study provides the first evidence of biosecurity management measures significantly decreasing the incidence of the ice-ice syndrome and pests on a commercial seaweed farm.

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Corrigendum to: The global Microcystis interactome - K.V. Cook; C. Li; H. Cai; L.R. Krumholz; K.D. Hambright; H.W. Paerl; M.M. Steffen; A.E. Wilson; M.A. Burford; H.‐P. Grossart; D. P. Hamilton; H. Jiang; et al. (Limnology and Oceanography, 2021)

The Influence of the Toxin-Producing Dinoflagellate, Alexandrium catenella (1119/27), on the Survival and Reproduction of the Marine Copepod, Acartia tonsa, During Prolonged Exposure - Ali H. Abdulhussain; Kathryn B. Cook; Andrew D. Turner; Adam M. Lewis; Thomas S. Bibby; Daniel J. Mayor (Frontiers in Marine Science, 2021)
Copepods can feed on, and may regulate, the blooms of harmful algae (HA), and may also facilitate dinoflagellate blooms by inducing toxin production and through selective grazing. However, exposure to HA may also cause mortality and reproductive impairment in copepods, with detrimental effects at the population-scale. Here we present the toxin profile of the dinoflagellate, Alexandrium catenella (formerly Alexandrium tamarense ), and examine how it affects the survival and reproduction of the cosmopolitan marine copepod, Acartia tonsa . Healthy adult copepods were exposed to mono-specific diets of toxic and non-toxic strains of A. catenella (1119/27 and 1119/19, respectively) and non-toxic Rhodomonas sp. for 10 days alongside unfed controls to examine how their survival was influenced by likely HA bloom conditions. Additional 2-day experiments examined how their egg production rate and hatching success were affected by food deprivation, toxic A. catenella , a non-toxic alternative and a mixture of toxic and non-toxic prey, at high and low concentrations. Survival of A. tonsa declined over the 10-day experiment in all treatments but was not significantly lower in the toxic A. catenella treatment; mortality was only significantly enhanced in the unfed animals, which showed 100% mortality after 9 days. Egg production rates and hatching success from females in the unfed and toxic A. catenella treatments were all significantly lower than values observed in females fed Rhodomonas sp. or non-toxic A. catenella . Animals offered 1,000 μg C L –1 of Rhodomonas sp. and a 50:50 mixture of toxic A. catenella and Rhodomonas sp. produced significantly more eggs than animals fed toxic A. catenella alone. These results were not apparent at prey concentrations of 100 μg C L –1 . The percentages of eggs to successfully hatch from females offered mono-specific diets of toxic A. catenella were always close to zero. Collectively, our results indicate that adult female A. tonsa can acquire sufficient energy from toxic A. catenella to survive, but suffer reproductive impairment when feeding on this prey alone.

Immersion challenge of naïve Atlantic salmon with cultured Nolandella sp. and Pseudoparamoeba sp. did not increase the severity of Neoparamoeba perurans ‐induced amoebic gill disease (AGD) - Chloe J. English; Natasha A. Botwright; Mark B. Adams; Andrew C. Barnes; James W. Wynne; Paula C. Lima; Mathew T. Cook (Journal of Fish Diseases, 2021)
Amoebic gill disease (AGD) is one of the main health issues impacting farmed Atlantic salmon. Neoparamoeba perurans causes AGD; however, a diversity of other amoeba species colonizes the gills and there is little understanding of whether they are commensal or potentially involved in different stages of gill disease development. Here, we conduct in vivo challenges of naïve Atlantic salmon with cultured Nolandella sp. and Pseudoparamoeba sp. to investigate their pathogenicity to Atlantic salmon gills. Additionally, we assessed whether the presence of Nolandella sp. and Pseudoparamoeba sp. influences the onset and/or severity of N. perurans ‐induced AGD. All three strains attached and multiplied on the gills according to qPCR analysis. Furthermore, minor gross gill lesions and histological changes were observed post‐exposure. While N. perurans was found associated with classical AGD lesions, Nolandella sp. and Pseudoparamoeba sp. were not found associated with lesion sites and these lesions did not meet the expected composite of histopathological changes for AGD. Moreover, the presence of these non‐ N. perurans species did not significantly increase the severity of AGD. This trial provides evidence that cultured Nolandella sp. and Pseudoparamoeba sp. do not induce AGD and do not influence the severity of AGD during the early stages of development.

A Multidisciplinary Approach to Investigate Deep-Pelagic Ecosystem Dynamics in the Gulf of Mexico Following Deepwater Horizon - April B. Cook; Andrea M. Bernard; Kevin M. Boswell; Heather Bracken-Grissom; Marta D’Elia; Sergio deRada; Cole G. Easson; David English; Ron I. Eytan; Tamara Frank; Chuanmin Hu; Matthew W. Johnston; et al. (Frontiers in Marine Science, 2020)
The pelagic Gulf of Mexico (GoM) is a complex system of dynamic physical oceanography (western boundary current, mesoscale eddies), high biological diversity, and community integration via diel vertical migration and lateral advection. Humans also heavily utilize this system, including its deep-sea components, for resource extraction, shipping, tourism, and other commercial activity. This utilization has had impacts, some with disastrous consequences. The Deepwater Horizon oil spill (DWHOS) occurred at a depth of ∼1500 m (Macondo wellhead), creating a persistent and toxic mixture of hydrocarbons and dispersant in the deep-pelagic (water column below 200 m depth) habitat. In order to assess the impacts of the DWHOS on this habitat, two large-scale research programs, described herein, were designed and executed. These programs, ONSAP and DEEPEND, aimed to quantitatively characterize the oceanic ecosystem of the northern GoM and to establish a time-series with which natural and anthropogenic changes could be detected. The approach was multi-disciplinary in nature and included in situ sampling, acoustic sensing, water column profiling and sampling, satellite remote sensing, AUV sensing, numerical modeling, genetic sequencing, and biogeochemical analyses. The synergy of these methodologies has provided new and unprecedented perspectives of an oceanic ecosystem with respect to composition, connectivity, drivers, and variability.

Biosecurity policy and legislation of the seaweed aquaculture industry in Tanzania - Sadock B. Rusekwa; Iona Campbell; Flower E. Msuya; Amelia S. Buriyo; Elizabeth J. Cottier-Cook (Journal of Applied Phycology, 2020)
Pest and disease outbreaks have significant impacts on the livelihoods of seaweed farmers each year, particularly in low- to middle-income countries around the world. Commercial seaweed farming of the red carrageenophytes, Eucheuma denticulatum , Kappaphycus alvarezii and Kappaphycus striatus , in Tanzania was established in 1989. The impacts of pests and diseases on the local seaweed industry had serious implications for the environment, society, local culture and human health. The industry was initially characterised by growth, but since 2002 has been severely limited due to pest and disease outbreaks, exacerbated by the effects of climate change. This paper identifies existing biosecurity frameworks in Tanzanian legislation and policies in order to assess their content regarding the management of pests and diseases in the seaweed industry. A total of thirteen frameworks were identified and analysed for their general biosecurity scope and inclusion of specific risks. Of the thirteen, only four were legally binding, and only four were identified to be applicable to the seaweed industry. National frameworks were predominantly designed to support finfish aquaculture; therefore, national authorities lack the expertise, experience and scientific basis on biosecurity issues in seaweed industry compared with other aquatic commercial commodities to identify and mitigate the risks from pest and disease outbreaks in the seaweed farming industry. Recommendations are provided to assist regulators in establishing biosecurity policies, which either explicitly include or are specifically designed, to support the Tanzanian seaweed industry. This analysis reveals where biosecurity capacity can be developed to support a sustainable and economically productive national seaweed farming industry.

A little SNP of this, a little SNP of that: The discovery of 116 single nucleotide polymorphism markers to enable the rapid identification of individual Pacific walrus (Odobenus rosmarus divergens) - Geoffrey M. Cook; Daniel J. Prince; Sean M. O’Rourke; Timothy L. King; Michael R. Miller; Cara J. Lewis; Michael S. Eackles; Patrick R. Lemons; Suresh A. Sethi; Jeffrey B. Olsen; John K. Wenburg (Conservation Genetics Resources, 2020)

Low Static Shear Modulus Along Foliation and Its Influence on the Elastic and Strength Anisotropy of Poorman Schist Rocks, Homestake Mine, South Dakota - Katherine J. Condon; Hiroki Sone; Herbert F. Wang; J. Ajo-Franklin; T. Baumgartner; K. Beckers; D. Blankenship; A. Bonneville; L. Boyd; S. Brown; J. A. Burghardt; C. Chai; et al. (Rock Mechanics and Rock Engineering, 2020)

Racial and ethnic differences in risk of second primary cancers among prostate cancer survivors - Diana R. Withrow; Sara J. Schonfeld; Rochelle E. Curtis; Lindsay M. Morton; Michael B. Cook; Eboneé N. Butler; Amy Berrington de González (Cancer Causes & Control, 2020)

An analysis of the current status and future of biosecurity frameworks for the Indonesian seaweed industry - Cicilia S. B. Kambey; Iona Campbell; Calvyn F. A. Sondak; Adibi R. M. Nor; Phaik E. Lim; Elizabeth J. Cottier-Cook (Journal of Applied Phycology, 2020)
Indonesia is the world largest producer of the red seaweeds Kappaphycus and Eucheuma ; however, this country is facing significant challenges such as disease outbreaks, epiphyte infestations and a loss in seedling quality. Biosecurity practices have been widely adopted in other aquaculture sectors and when enforced can help to limit the introduction and spread of diseases and pests. To assess current capacity for biosecurity in seaweed aquaculture in Indonesia, a systematic analysis of policy frameworks including legislation, regulatory tools, and national standards was conducted. Biosecurity themes and risks were used to evaluate current national biosecurity content. The results identified major challenges faced by the industry in order to implement biosecurity policies in practice. Barriers to implementation included unspecific reference to the seaweed aquaculture sector, limited variety of approaches to biosecurity, limited use of up-to-date scientific evidence, insufficient guidance for the use of precaution and insufficient inclusion of specific biosecurity hazards. In general, although national regulations are currently under revision, current policies indicate a lack of clarity where biosecurity is included. Six recommendations are suggested to incorporate proactive biosecurity actions into current frameworks, with the aim of improving the health and sustainability of the seaweed aquaculture sector in Indonesia.

Biosecurity policy and legislation for the global seaweed aquaculture industry - Iona Campbell; Cicilia S. B. Kambey; Jonalyn P. Mateo; Sadock B. Rusekwa; Anicia Q. Hurtado; Flower E. Msuya; Grant D. Stentiford; Elizabeth J. Cottier-Cook (Journal of Applied Phycology, 2020)
Each year a significant proportion of global food production is lost to pests and diseases, with concerted efforts by government and industry focussed on application of effective biosecurity policies which attempt to minimise their emergence and spread. In aquaculture the volume of seaweeds produced is second only to farmed fish and red algal carrageenophytes currently represent approximately 42% of global production of all seaweeds. Despite this importance, expansion of the seaweed sector is increasingly limited by the high prevalence of recalcitrant diseases and epiphytic pests with potential to emerge and with the demonstrated propensity to spread, particularly in the absence of effective national and international biosecurity policies. Developing biosecurity policy and legislation to manage biosecurity risk in seaweed aquaculture is urgently required to limit these impacts. To understand current international biosecurity frameworks and their efficacy, existing legislative frameworks were analysed quantitatively for the content of biosecurity measures, applicability to the seaweed industry, and inclusion of risks posed by diseases, pests and non-native species. Deficiencies in existing frameworks included the following: inconsistent terminology for inclusion of cultivated seaweeds, unclear designation of implementation responsibility, insufficient evidence-based information and limited alignment of biosecurity hazards and risks. Given the global importance of the cultivation of various seaweeds in alleviating poverty in low and middle income countries, it is crucial that the relatively low-unit value of the industry (i.e. as compared with other aquatic animal sectors) should not conflate with a perceived low risk of disease or pest transfer, nor the subsequent economic and environmental impact that disease transfer may impact on receiving nations (well beyond their seaweed operations). Developing a clear basis for development of robust international biosecurity policies related to the trade in seaweeds arising from the global aquaculture industry, by first addressing the gaps highlighted in this study, will be crucial in limiting impacts of pests and diseases on this valuable industry and on natural capital in locations where seaweeds are farmed.

Fitness, independent of physical activity is associated with cerebral blood flow in adults at risk for Alzheimer’s disease - Ryan J. Dougherty; Elizabeth A. Boots; Jacob B. Lindheimer; Aaron J. Stegner; Stephanie Van Riper; Dorothy F. Edwards; Catherine L. Gallagher; Cynthia M. Carlsson; Howard A. Rowley; Barbara B. Bendlin; Sanjay Asthana; Bruce P. Hermann; et al. (Brain Imaging and Behavior, 2020)

Simulating alternative sustainable water futures - D. A. Sampson; E. M. Cook; M. J. Davidson; N. B. Grimm; D. M. Iwaniec (Sustainability Science, 2020)

Toward the Integrated Marine Debris Observing System - Nikolai Maximenko; Paolo Corradi; Kara Lavender Law; Erik Van Sebille; Shungudzemwoyo P. Garaba; Richard Stephen Lampitt; Francois Galgani; Victor Martinez-Vicente; Lonneke Goddijn-Murphy; Joana Mira Veiga; Richard C. Thompson; Christophe Maes; et al. (Frontiers in Marine Science, 2019)

The state of Western Australia’s coral reefs - James P. Gilmour; Kylie L. Cook; Nicole M. Ryan; Marjetta L. Puotinen; Rebecca H. Green; George Shedrawi; Jean-Paul A. Hobbs; Damian P. Thomson; Russell C. Babcock; Joanna Buckee; Taryn Foster; Zoe T. Richards; et al. (Coral Reefs, 2019)

Small Animal Multivariate Brain Analysis (SAMBA) – a High Throughput Pipeline with a Validation Framework - Robert J. Anderson; James J. Cook; Natalie Delpratt; John C. Nouls; Bin Gu; James O. McNamara; Brian B. Avants; G. Allan Johnson; Alexandra Badea (Neuroinformatics, 2019)

Implementation of a Systematic Tumor Screening Program for Lynch Syndrome in an Integrated Health Care Setting - Elizabeth V. Clarke; Kristin R. Muessig; Jamilyn Zepp; Jessica E. Hunter; Sapna Syngal; Louise S. Acheson; Georgia L. Wiesner; Susan K. Peterson; Kellene M. Bergen; Elizabeth Shuster; James V. Davis; Jennifer L. Schneider; et al. (Familial Cancer, 2019)

How do climate change experiments alter plot‐scale climate? - A. K. Ettinger; I. Chuine; B. I. Cook; J. S. Dukes; A. M. Ellison; M. R. Johnston; A. M. Panetta; C. R. Rollinson; Y. Vitasse; E. M. Wolkovich (Ecology Letters, 2019)
To understand and forecast biological responses to climate change, scientists frequently use field experiments that alter temperature and precipitation. Climate manipulations can manifest in complex ways, however, challenging interpretations of biological responses. We reviewed publications to compile a database of daily plot‐scale climate data from 15 active‐warming experiments. We find that the common practices of analysing treatments as mean or categorical changes (e.g. warmed vs. unwarmed) masks important variation in treatment effects over space and time. Our synthesis showed that measured mean warming, in plots with the same target warming within a study, differed by up to 1.6 C (63% of target), on average, across six studies with blocked designs. Variation was high across sites and designs: for example, plots differed by 1.1 C (47% of target) on average, for infrared studies with feedback control ( n = 3) vs. by 2.2 C (80% of target) on average for infrared with constant wattage designs ( n = 2). Warming treatments produce non‐temperature effects as well, such as soil drying. The combination of these direct and indirect effects is complex and can have important biological consequences. With a case study of plant phenology across five experiments in our database, we show how accounting for drier soils with warming tripled the estimated sensitivity of budburst to temperature. We provide recommendations for future analyses, experimental design, and data sharing to improve our mechanistic understanding from climate change experiments, and thus their utility to accurately forecast species’ responses.

Training Needs of Clinical and Research Professionals to Optimize Minority Recruitment and Retention in Cancer Clinical Trials - Soumya J. Niranjan; Raegan W. Durant; Jennifer A. Wenzel; Elise D. Cook; Mona N. Fouad; Selwyn M. Vickers; Badrinath R. Konety; Sarah B. Rutland; Zachary R. Simoni; Michelle Y. Martin (Journal of Cancer Education, 2019)

Applying the principles of isotope analysis in plant and animal ecology to forensic science in the Americas - Lesley A. Chesson; Janet E. Barnette; Gabriel J. Bowen; J. Renée Brooks; John F. Casale; Thure E. Cerling; Craig S. Cook; Charles B. Douthitt; John D. Howa; Janet M. Hurley; Helen W. Kreuzer; Michael J. Lott; et al. (Oecologia, 2018)

Expansion of landscape characterisation methods within the Hydrogeological Landscape Framework: application in the Australian Capital Territory - A. L. Cowood; C. L. Moore; M. J. Cracknell; J. Young; R. Muller; A. T. Nicholson; A. C. Wooldridge; B. R. Jenkins; W. Cook (Australian Journal of Earth Sciences, 2017)

Influence of oceanographic conditions on abundance and distribution of post‐larval and juvenile carangid fishes in the northern Gulf of Mexico - John A. Mohan; Tracey T. Sutton; April B. Cook; Kevin M. Boswell; R. J. David Wells (Fisheries Oceanography, 2017)
Relationships between abundance of post‐larval and juvenile carangid (jacks) fishes and physical oceanographic conditions were examined in the northern Gulf of Mexico (GoM) in 2011 with high freshwater input from the Mississippi River. Generalized additive models ( GAM s) were used to explore complex relationships between carangid abundance and physical oceanographic data of sea surface temperature ( SST ), sea surface height anomaly ( SSHA ) and salinity. The five most abundant carangid species collected were: Selene setapinnis (34%); Caranx crysos (30%); Caranx hippos (10%); Chloroscombrus chrysurus (9%) and Trachurus lathami (8%). Post‐larval carangids (median standard length [ SL ] = 10 mm) were less abundant during the spring and early summer, but more abundant during the late summer and fall, suggesting summer to fall spawning for most species. Juvenile carangid (median SL = 23 mm) abundance also increased between the mid‐summer and early fall. Most species showed increased abundance at lower salinities and higher temperatures, suggesting entrainment of post‐larval fishes or feeding aggregations of juveniles at frontal convergence zones between the expansive river plume and dynamic mesoscale eddy water masses. However, responses were species‐ and life‐stage specific, which may indicate fine‐scale habitat partitioning between species. Ordination methods also revealed higher carangid abundances at lower salinities for both post‐larval and juvenile life stages, with species‐ and life‐stage specific responses to SST and SSHA , further suggesting habitat separation between species. Results indicate strong links between physical oceanographic features and carangid distributions in the dynamic northern GoM.

Universal screening for Lynch syndrome among patients with colorectal cancer: patient perspectives on screening and sharing results with at-risk relatives - Jessica Ezzell Hunter; Kathleen A. Arnold; Jennifer E. Cook; Jamilyn Zepp; Marian J. Gilmore; Alan F. Rope; James V. Davis; Kellene M. Bergen; Elizabeth Esterberg; Kristin R. Muessig; Susan K. Peterson; Sapna Syngal; et al. (Familial Cancer, 2017)

A longitudinal study of patients with cirrhosis treated with L-ornithine L-aspartate, examined with magnetization transfer, diffusion-weighted imaging and magnetic resonance spectroscopy - Vijay P. B. Grover; Mark J. W. McPhail; Marzena Wylezinska-Arridge; Mary M. E. Crossey; Julie A. Fitzpatrick; Louise Southern; Brian K. Saxby; Nicola A. Cook; I. Jane Cox; Adam D. Waldman; Novraj S. Dhanjal; Aluel Bak-Bol; et al. (Metabolic Brain Disease, 2017)

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

Flood risk management, an approach to managing cross-border hazards - L. J. Bracken; E. A. Oughton; A. Donaldson; B. Cook; J. Forrester; C. Spray; S. Cinderby; D. Passmore; N. Bissett (Natural Hazards, 2016)

A trans‐Atlantic examination of haddock Melanogrammus aeglefinus food habits - J. C. Tam; J. S. Link; S. I. Large; B. Bogstad; A. Bundy; A. M. Cook; G. E. Dingsør; A. V. Dolgov; D. Howell; A. Kempf; J. K. Pinnegar; A. Rindorf; et al. (Journal of Fish Biology, 2016)
The food habits of Melanogrammus aeglefinus were explored and contrasted across multiple north‐eastern and north‐western Atlantic Ocean ecosystems, using databases that span multiple decades. The results show that among all ecosystems, echinoderms are a consistent part of M. aeglefinus diet, but patterns emerge regarding where and when M. aeglefinus primarily eat fishes v . echinoderms. Melanogrammus aeglefinus does not regularly exhibit the increase in piscivory with ontogeny that other gadoids often show, and in several ecosystems there is a lower occurrence of piscivory. There is an apparent inverse relationship between the consumption of fishes and echinoderms in M. aeglefinus over time, where certain years show high levels of one prey item and low levels of the other. This apparent binary choice can be viewed as part of a gradient of prey options, contingent upon a suite of factors external to M. aeglefinus dynamics. The energetic consequences of this prey choice are discussed, noting that in some instances it may not be a choice at all.

Development and characterization of a synthetic infectious cDNA clone of the virulent Bucyrus strain of equine arteritis virus expressing mCherry (red fluorescent protein) - Shankar P. Mondal; R. Frank Cook; R. Lakshman Chelvarajan; Pamela J. Henney; Peter J. Timoney; Udeni B. R. Balasuriya (Archives of Virology, 2016)

Postmagmatic magnetite–apatite assemblage in mafic intrusions: a case study of dolerite at Olympic Dam, South Australia - Olga B. Apukhtina; Vadim S. Kamenetsky; Kathy Ehrig; Maya B. Kamenetsky; Jocelyn McPhie; Roland Maas; Sebastien Meffre; Karsten Goemann; Thomas Rodemann; Nigel J. Cook; Cristiana L. Ciobanu (Contributions to Mineralogy and Petrology, 2016)

Evidence of climate‐driven ecosystem reorganization in the Gulf of Mexico - Mandy Karnauskas; Michael J. Schirripa; J. K. Craig; Geoffrey S. Cook; Christopher R. Kelble; Juan J. Agar; Bryan A. Black; David B. Enfield; David Lindo‐Atichati; Barbara A. Muhling; Kevin M. Purcell; Paul M. Richards; et al. (Global Change Biology, 2015)
The Gulf of Mexico is one of the most ecologically and economically valuable marine ecosystems in the world and is affected by a variety of natural and anthropogenic phenomena including climate, hurricanes, coastal development, agricultural runoff, oil spills, and fishing. These complex and interacting stressors, together with the highly dynamic nature of this ecosystem, present challenges for the effective management of its resources. We analyze a compilation of over 100 indicators representing physical, biological, and economic aspects of the Gulf of Mexico and find that an ecosystem‐wide reorganization occurred in the mid‐1990s. Further analysis of fishery landings composition data indicates a major shift in the late 1970s coincident with the advent of US national fisheries management policy, as well as significant shifts in the mid‐1960s and the mid‐1990s. These latter shifts are aligned temporally with changes in a major climate mode in the Atlantic Ocean: the Atlantic Multidecadal Oscillation ( AMO ). We provide an explanation for how the AMO may drive physical changes in the Gulf of Mexico, thus altering higher‐level ecosystem dynamics. The hypotheses presented here should provide focus for further targeted studies, particularly in regard to whether and how management should adjust to different climate regimes or states of nature. Our study highlights the challenges in understanding the effects of climatic drivers against a background of multiple anthropogenic pressures, particularly in a system where these forces interact in complex and nonlinear ways.

Sex differences in ventricular–vascular coupling following endurance training - A. D. Lane; H. Yan; S. M. Ranadive; R. M. Kappus; P. Sun; M. D. Cook; I. Harvey; J. Woods; K. Wilund; B. Fernhall (European Journal of Applied Physiology, 2014)

Temporal ecology in the Anthropocene - E. M. Wolkovich; B. I. Cook; K. K. McLauchlan; T. J. Davies (Ecology Letters, 2014)
Two fundamental axes – space and time – shape ecological systems. Over the last 30 years spatial ecology has developed as an integrative, multidisciplinary science that has improved our understanding of the ecological consequences of habitat fragmentation and loss. We argue that accelerating climate change – the effective manipulation of time by humans – has generated a current need to build an equivalent framework for temporal ecology. Climate change has at once pressed ecologists to understand and predict ecological dynamics in non‐stationary environments, while also challenged fundamental assumptions of many concepts, models and approaches. However, similarities between space and time, especially related issues of scaling, provide an outline for improving ecological models and forecasting of temporal dynamics, while the unique attributes of time, particularly its emphasis on events and its singular direction, highlight where new approaches are needed. We emphasise how a renewed, interdisciplinary focus on time would coalesce related concepts, help develop new theories and methods and guide further data collection. The next challenge will be to unite predictive frameworks from spatial and temporal ecology to build robust forecasts of when and where environmental change will pose the largest threats to species and ecosystems, as well as identifying the best opportunities for conservation.

Erratum to: A genome-wide association study of prostate cancer in West African men - Michael Blaise Cook; Zhaoming Wang; Edward D. Yeboah; Yao Tettey; Richard B. Biritwum; Andrew A. Adjei; Evelyn Tay; Ann Truelove; Shelley Niwa; Charles C. Chung; Annand P. Chokkalingam; Lisa W. Chu; et al. (Human Genetics, 2014)

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

A genome-wide association study of prostate cancer in West African men - Michael Blaise Cook; Zhaoming Wang; Edward D. Yeboah; Yao Tettey; Richard B. Biritwum; Andrew A. Adjei; Evelyn Tay; Ann Truelove; Shelley Niwa; Charles C. Chung; Annand P. Chokkalingam; Lisa W. Chu; et al. (Human Genetics, 2014)

Genome-wide association study of endometrial cancer in E2C2 - Immaculata De Vivo; Jennifer Prescott; Veronica Wendy Setiawan; Sara H. Olson; Nicolas Wentzensen; John Attia; Amanda Black; Louise Brinton; Chu Chen; Constance Chen; Linda S. Cook; Marta Crous-Bou; et al. (Human Genetics, 2014)

Effect of cryotherapy on muscle recovery and inflammation following a bout of damaging exercise - Naomi J. Crystal; David H. Townson; Summer B. Cook; Dain P. LaRoche (European Journal of Applied Physiology, 2013)

A comparison of culture-dependent and culture-independent techniques used to characterize bacterial communities on healthy and white plague-diseased corals of the Montastraea annularis species complex - G. M. Cook; J. P. Rothenberger; M. Sikaroodi; P. M. Gillevet; E. C. Peters; R. B. Jonas (Coral Reefs, 2013)

Alpine cushion plants inhibit the loss of phylogenetic diversity in severe environments - B. J. Butterfield; L. A. Cavieres; R. M. Callaway; B. J. Cook; Z. Kikvidze; C. J. Lortie; R. Michalet; F. I. Pugnaire; C. Schöb; S. Xiao; B. Zaitchek; F. Anthelme; et al. (Ecology Letters, 2013)
Biotic interactions can shape phylogenetic community structure (PCS). However, we do not know how the asymmetric effects of foundation species on communities extend to effects on PCS. We assessed PCS of alpine plant communities around the world, both within cushion plant foundation species and adjacent open ground, and compared the effects of foundation species and climate on alpha (within‐microsite), beta (between open and cushion) and gamma (open and cushion combined) PCS. In the open, alpha PCS shifted from highly related to distantly related with increasing potential productivity. However, we found no relationship between gamma PCS and climate, due to divergence in phylogenetic composition between cushion and open sub‐communities in severe environments, as demonstrated by increasing phylo‐beta diversity. Thus, foundation species functioned as micro‐refugia by facilitating less stress‐tolerant lineages in severe environments, erasing a global productivity – phylogenetic diversity relationship that would go undetected without accounting for this important biotic interaction.

A comparative gradient approach as a tool for understanding and managing urban ecosystems - Christopher G. Boone; Elizabeth Cook; Sharon J. Hall; Marcia L. Nation; Nancy B. Grimm; Carol B. Raish; Deborah M. Finch; Abigail M. York (Urban Ecosystems, 2012)

Sensitivity of Spring Phenology to Warming Across Temporal and Spatial Climate Gradients in Two Independent Databases - Benjamin I. Cook; Elizabeth M. Wolkovich; T. Jonathan Davies; Toby R. Ault; Julio L. Betancourt; Jenica M. Allen; Kjell Bolmgren; Elsa E. Cleland; Theresa M. Crimmins; Nathan J. B. Kraft; Lesley T. Lancaster; Susan J. Mazer; et al. (Ecosystems, 2012)

Parameter and uncertainty estimation for process‐oriented population and distribution models: data, statistics and the niche - Glenn Marion; Greg J. McInerny; Jörn Pagel; Stephen Catterall; Alex R. Cook; Florian Hartig; Robert B. O'Hara (Journal of Biogeography, 2012)
The spatial distribution of a species is determined by dynamic processes such as reproduction, mortality and dispersal. Conventional static species distribution models (SDMs) do not incorporate these processes explicitly. This limits their applicability, particularly for non‐equilibrium situations such as invasions or climate change. In this paper we show how dynamic SDMs can be formulated and fitted to data within a Bayesian framework. Our focus is on discrete state‐space Markov process models which provide a flexible framework to account for stochasticity in key demographic processes, including dispersal, growth and competition. We show how to construct likelihood functions for such models (both discrete and continuous time versions) and how these can be combined with suitable observation models to conduct Bayesian parameter inference using computational techniques such as Markov chain Monte Carlo. We illustrate the current state‐of‐the‐art with three contrasting examples using both simulated and empirical data. The use of simulated data allows the robustness of the methods to be tested with respect to deficiencies in both data and model. These examples show how mechanistic understanding of the processes that determine distribution and abundance can be combined with different sources of information at a range of spatial and temporal scales. Application of such techniques will enable more reliable inference and projections, e.g. under future climate change scenarios than is possible with purely correlative approaches. Conversely, confronting such process‐oriented niche models with abundance and distribution data will test current understanding and may ultimately feedback to improve underlying ecological theory.

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

Reconciling estimates of the contemporary North American carbon balance among terrestrial biosphere models, atmospheric inversions, and a new approach for estimating net ecosystem exchange from inventory‐based data - Daniel J. Hayes; David P. Turner; Graham Stinson; A. David McGuire; Yaxing Wei; Tristram O. West; Linda S. Heath; Bernardus de Jong; Brian G. McConkey; Richard A. Birdsey; Werner A. Kurz; Andrew R. Jacobson; et al. (Global Change Biology, 2012)
We develop an approach for estimating net ecosystem exchange ( NEE ) using inventory‐based information over North America ( NA ) for a recent 7‐year period (ca. 2000–2006). The approach notably retains information on the spatial distribution of NEE , or the vertical exchange between land and atmosphere of all non‐fossil fuel sources and sinks of CO 2 , while accounting for lateral transfers of forest and crop products as well as their eventual emissions. The total NEE estimate of a −327 ± 252 TgC yr −1 sink for NA was driven primarily by CO 2 uptake in the Forest Lands sector (−248 TgC yr −1 ), largely in the Northwest and Southeast regions of the US, and in the Crop Lands sector (−297 TgC yr −1 ), predominantly in the Midwest US states. These sinks are counteracted by the carbon source estimated for the Other Lands sector (+218 TgC yr −1 ), where much of the forest and crop products are assumed to be returned to the atmosphere (through livestock and human consumption). The ecosystems of Mexico are estimated to be a small net source (+18 TgC yr −1 ) due to land use change between 1993 and 2002. We compare these inventory‐based estimates with results from a suite of terrestrial biosphere and atmospheric inversion models, where the mean continental‐scale NEE estimate for each ensemble is −511 TgC yr −1 and −931 TgC yr −1 , respectively. In the modeling approaches, all sectors, including Other Lands, were generally estimated to be a carbon sink, driven in part by assumed CO 2 fertilization and/or lack of consideration of carbon sources from disturbances and product emissions. Additional fluxes not measured by the inventories, although highly uncertain, could add an additional −239 TgC yr −1 to the inventory‐based NA sink estimate, thus suggesting some convergence with the modeling approaches.

An Open Source Multivariate Framework for n-Tissue Segmentation with Evaluation on Public Data - Brian B. Avants; Nicholas J. Tustison; Jue Wu; Philip A. Cook; James C. Gee (Neuroinformatics, 2011)

Predicting phenology by integrating ecology, evolution and climate science - Stephanie Pau; Elizabeth M. Wolkovich; Benjamin I. Cook; T. Jonathan Davies; Nathan J. B. Kraft; Kjell Bolmgren; Julio L. Betancourt; Elsa E. Cleland (Global Change Biology, 2011)
Forecasting how species and ecosystems will respond to climate change has been a major aim of ecology in recent years. Much of this research has focused on phenology – the timing of life‐history events. Phenology has well‐demonstrated links to climate, from genetic to landscape scales; yet our ability to explain and predict variation in phenology across species, habitats and time remains poor. Here, we outline how merging approaches from ecology, climate science and evolutionary biology can advance research on phenological responses to climate variability. Using insight into seasonal and interannual climate variability combined with niche theory and community phylogenetics, we develop a predictive approach for species’ reponses to changing climate. Our approach predicts that species occupying higher latitudes or the early growing season should be most sensitive to climate and have the most phylogenetically conserved phenologies. We further predict that temperate species will respond to climate change by shifting in time, while tropical species will respond by shifting space, or by evolving. Although we focus here on plant phenology, our approach is broadly applicable to ecological research of plant responses to climate variability.

Haplotype structure in Ashkenazi Jewish BRCA1 and BRCA2 mutation carriers - Kate M. Im; Tomas Kirchhoff; Xianshu Wang; Todd Green; Clement Y. Chow; Joseph Vijai; Joshua Korn; Mia M. Gaudet; Zachary Fredericksen; V. Shane Pankratz; Candace Guiducci; Andrew Crenshaw; et al. (Human Genetics, 2011)

The potential to reconstruct broadscale climate indices associated with southeast Australian droughts from Athrotaxis species, Tasmania - K. J. Allen; J. Ogden; B. M. Buckley; E. R. Cook; P. J. Baker (Climate Dynamics, 2011)

The Importance of Termites to the CH4 Balance of a Tropical Savanna Woodland of Northern Australia - Hiz Jamali; Stephen J. Livesley; Samantha P. Grover; Tracy Z. Dawes; Lindsay B. Hutley; Garry D. Cook; Stefan K. Arndt (Ecosystems, 2011)

You are what you eat, whenever or wherever you eat it: an integrative analysis of fish food habits in Canadian and U.S.A. waters - A. Bundy; J. S. Link; B. E. Smith; A. M. Cook (Journal of Fish Biology, 2011)
The degree to which fish diet differs by season and area, particularly over broad scales, was examined for the first time in temperate, contiguous north‐west Atlantic Ocean waters by comparing food habit data for 10 species of fishes collected concurrently during the spring and autumn surveys in the U.S.A. (Gulf of Maine proper and Georges Bank) and in the summer survey in Canada (western Scotian Shelf and Bay of Fundy). For most species, there was a general concurrence among the three seasons and four areas: summer diets had the same dominant prey items as spring and autumn diets. Although a suite of multivariate analyses did elucidate some differences in specific proportions of the diet for these species across seasons and areas, the main prey did not substantially change for most of these species. These results suggest that there are (1) minimal differences in diet across season for these species at these taxonomic resolutions, (2) there are minimal differences in diet geographically for these species and (3) differences across species, as expected, are important. Many fisheries ecosystem and multispecies models are dependent on food habit data, where resolving seasonal and spatial differences in diet remains an important consideration; however, the present work implies that amalgamated estimates of diet from seasonal surveys may be a reasonable approach when no finer seasonal resolution exists, as long as due diligence is exercised.

Seizure Detection Using Seizure Probability Estimation: Comparison of Features Used to Detect Seizures - Levin Kuhlmann; Anthony N. Burkitt; Mark J. Cook; Karen Fuller; David B. Grayden; Linda Seiderer; Iven M. Y. Mareels (Annals of Biomedical Engineering, 2009)

Respiratory Irritants in Australian Bushfire Smoke: Air Toxics Sampling in a Smoke Chamber and During Prescribed Burns - Annemarie J. B. M. De Vos; Fabienne Reisen; Angus Cook; Brian Devine; Philip Weinstein (Archives of Environmental Contamination and Toxicology, 2009)

Resolving relationships in some African fungus-growing termites (Termitidae, Macrotermitinae) using molecular phylogeny, morphology, and field parameters - J. P. E. C. Darlington; R. B. Benson; C. E. Cook; G. Walker (Insectes Sociaux, 2008)

Genetic variants in the 8q24 locus and risk of testicular germ cell tumors - Michael B. Cook; Barry I. Graubard; Sabah M. Quraishi; Meredith Yeager; Stephen J. Chanock; Andrew Crenshaw; Ralph L. Erickson; Mark V. Rubertone; Gilles Thomas; Katherine A. McGlynn (Human Genetics, 2008)

Relationship Between the Endophyte Embellisia spp. and the Toxic Alkaloid Swainsonine in Major Locoweed Species (Astragalus and Oxytropis) - M. H. Ralphs; R. Creamer; D. Baucom; D. R. Gardner; S. L. Welsh; J. D. Graham; C. Hart; D. Cook; B. L. Stegelmeier (Journal of Chemical Ecology, 2008)

Comparative phylogeography and demographic history of the wood lemming ( Myopus schisticolor ): implications for late Quaternary history of the taiga species in Eurasia - V. B. FEDOROV; A. V. GOROPASHNAYA; G. G. BOESKOROV; J. A. COOK (Molecular Ecology, 2008)
The association between demographic history, genealogy and geographical distribution of mitochondrial DNA cytochrome b haplotypes was studied in the wood lemming ( Myopus schisticolor ), a species that is closely associated with the boreal forest of the Eurasian taiga zone from Scandinavia to the Pacific coast. Except for a major phylogeographic discontinuity (0.9% nucleotide divergence) in southeastern Siberia, only shallow regional genetic structure was detected across northern Eurasia. Genetic signs of demographic expansions imply that successive range contractions and expansions on different spatial scales represented the primary historical events that shaped geographical patterns of genetic variation. Comparison of phylogeographic structure across a taxonomically diverse array of other species that are ecologically associated with the taiga forest revealed similar patterns and identified two general aspects. First, the major south–north phylogeographic discontinuity observed in five out of six species studied in southeastern Siberia and the Far East implies vicariant separation in two different refugial areas. The limited distribution range of the southeastern lineages provides no evidence of the importance of the putative southeastern refugial area for postglacial colonization of northern Eurasia by boreal forest species. Second, the lack of phylogeographic structure associated with significant reciprocal monophyly and genetic signatures of demographic expansion in all nine boreal forest animal species studied to date across most of northern Eurasia imply contraction of each species to a single refugial area during the late Pleistocene followed by range expansion on a continental scale. Similar phylogeographic patterns observed in this taxonomically diverse set of organisms with different life histories and dispersal potentials reflect the historical dynamics of their shared environment, the taiga forest in northern Eurasia.

CO 2 balance of boreal, temperate, and tropical forests derived from a global database - S. LUYSSAERT; I. INGLIMA; M. JUNG; A. D. RICHARDSON; M. REICHSTEIN; D. PAPALE; S. L. PIAO; E. ‐D. SCHULZE; L. WINGATE; G. MATTEUCCI; L. ARAGAO; M. AUBINET; et al. (Global Change Biology, 2007)
Terrestrial ecosystems sequester 2.1 Pg of atmospheric carbon annually. A large amount of the terrestrial sink is realized by forests. However, considerable uncertainties remain regarding the fate of this carbon over both short and long timescales. Relevant data to address these uncertainties are being collected at many sites around the world, but syntheses of these data are still sparse. To facilitate future synthesis activities, we have assembled a comprehensive global database for forest ecosystems, which includes carbon budget variables (fluxes and stocks), ecosystem traits (e.g. leaf area index, age), as well as ancillary site information such as management regime, climate, and soil characteristics. This publicly available database can be used to quantify global, regional or biome‐specific carbon budgets; to re‐examine established relationships; to test emerging hypotheses about ecosystem functioning [e.g. a constant net ecosystem production (NEP) to gross primary production (GPP) ratio]; and as benchmarks for model evaluations. In this paper, we present the first analysis of this database. We discuss the climatic influences on GPP, net primary production (NPP) and NEP and present the CO 2 balances for boreal, temperate, and tropical forest biomes based on micrometeorological, ecophysiological, and biometric flux and inventory estimates. Globally, GPP of forests benefited from higher temperatures and precipitation whereas NPP saturated above either a threshold of 1500 mm precipitation or a mean annual temperature of 10 °C. The global pattern in NEP was insensitive to climate and is hypothesized to be mainly determined by nonclimatic conditions such as successional stage, management, site history, and site disturbance. In all biomes, closing the CO 2 balance required the introduction of substantial biome‐specific closure terms. Nonclosure was taken as an indication that respiratory processes, advection, and non‐CO 2 carbon fluxes are not presently being adequately accounted for.

Behavioural and chemical ecology underlying the success of turnip rape (Brassica rapa) trap crops in protecting oilseed rape (Brassica napus) from the pollen beetle (Meligethes aeneus) - S. M. Cook; H. B. Rasmussen; M. A. Birkett; D. A. Murray; B. J. Pye; N. P. Watts; I. H. Williams (Arthropod-Plant Interactions, 2007)

Allelic and haplotypic diversity at the major histocompatibility class II within domesticated Australian Atlantic salmon ( Salmo salar L.) - J. W. Wynne; M. T. Cook; B. H. Holmes; N. G. Elliott (Journal of Fish Biology, 2007)
Variation within the major histocompatibility (MH) class II alpha gene ( Sasa‐DAA ) was compared between domesticated Australian Atlantic salmon and their ancestral Canadian population. The level of Sasa‐DAA and MH class II beta gene ( Sasa‐DAB ) sequence variation was also examined within the Australian population and compared with that published for European Atlantic salmon populations. In contrast to variation previously reported for non‐coding microsatellite loci, a high level of MH class II allelic variation has been maintained within the domesticated Australian populations. Furthermore, a high level of Sasa‐DAA and Sasa‐DAB allele sequence diversity was also observed and exceeded that reported for other cultured Atlantic salmon populations. The number of Sasa‐DAB allele sequences (14) surpassed the number of Sasa‐DAA allele sequences (9) to produce 14 unique class II haplotypes. We conclude that the Australian Atlantic salmon populations show high MH class II allelic and haplotypic variation compared with both its ancestral Canadian population and other cultured Atlantic salmon populations.

Biogeographic history of an Australian freshwater shrimp, Paratya australiensis (Atyidae): the role life history transition in phylogeographic diversification - B. D. COOK; A. M. BAKER; T. J. PAGE; S. C. GRANT; J. H. FAWCETT; D. A. HURWOOD; J. M. HUGHES (Molecular Ecology, 2006)
The widespread distribution of the freshwater shrimp Paratya australiensis in eastern Australia suggests that populations of this species have been connected in the past. Amphidromy is ancestral in these shrimps, although many extant populations are known to be restricted to freshwater habitats. In this study, we used a fragment of the cytochrome c oxidase I mitochondrial DNA (mtDNA) gene to examine diversity within P. australiensis and to assess the relative importance of amphidromy in its evolutionary history. We hypothesized that if transitions from an amphidromous to a freshwater life history were important, then we would find a number of divergent lineages restricted to single or groups of nearby drainages. Alternatively, if amphidromy was maintained within the species historically, we expected to find lineages distributed over many drainages. We assumed that the only way for divergence to occur within amphidromous lineages was if dispersal was limited to between nearby estuaries, which, during arid periods in the earth's history, became isolated from one another. We found nine highly divergent mtDNA lineages, estimated to have diverged from one another in the late Miocene/early Pliocene, when the climate was more arid than at present. Despite this, the geographic distribution of lineages and haplotypes within lineages did not support the notion of a stepping‐stone model of dispersal between estuaries. We conclude that the extensive divergence has most likely arisen through a number of independent amphidromy–freshwater life history transitions, rather than via historical isolation of amphidromy populations. We also found evidence for extensive movement between coastal and inland drainages, supporting the notion that secondary contact between lineages may have occurred as a result of drainage rearrangements. Finally, our data indicate that P. australiensis is likely a complex of cryptic species, some of which are widely distributed, and others geographically restricted.

Field-Scale Experiments for Site-Specific Crop Management. Part II: A Geostatistical Analysis - M. J. Pringle; A. B. McBratney; S. E. Cook (Precision Agriculture, 2004)

Field-Scale Experiments for Site-Specific Crop Management. Part I: Design Considerations - M. J. Pringle; S. E. Cook; A. B. McBratney (Precision Agriculture, 2004)

Analysis of soil wetting and solute transport in subsurface trickle irrigation - Claire M. Cote; Keith L. Bristow; Philip B. Charlesworth; Freeman J. Cook; Peter J. Thorburn (Irrigation Science, 2003)

Holarctic phylogeography of the root vole ( Microtus oeconomus ): implications for late Quaternary biogeography of high latitudes - C. Brunhoff; K. E. Galbreath; V. B. Fedorov; J. A. Cook; M. Jaarola (Molecular Ecology, 2003)
A species‐wide phylogeographical study of the root vole ( Microtus oeconomus ) was performed using the whole 1140 base pair mitochondrial (mt) cytochrome b gene. We examined 83 specimens from 52 localities resulting in 65 unique haplotypes. Our results demonstrate that the root vole is divided into four main mtDNA phylogenetic lineages that seem to have largely allopatric distributions. Net divergence estimates (2.0–3.5%) between phylogroups, as well as relatively high nucleotide diversity estimates within phylogroups, indicate that the distinct phylogeographical structure was initiated by historical events that predated the latest glaciation. European root voles are divided into a Northern and a Central mtDNA phylogroup. The mtDNA data in concert with fossil records imply that root voles remained north of the classical refugial areas in southern Europe during the last glacial period. The currently fragmented populations in central Europe belong to a single mtDNA phylogroup. The Central Asian and the North European lineages are separated by the Ural Mountains, a phylogeographical split also found in collared lemmings ( Dicrostonyx ) and the common vole ( M. arvalis ). The Beringian lineage occurs from eastern Russia through Alaska to northwestern Canada. This distribution is congruent with the traditional boundaries of the Beringian refugium and with phylogeographical work on other organisms. In conclusion, similarities between the phylogeographical patterns in the root vole and other rodents, such as Arctic and subarctic lemmings, as well as more temperate vole species, indicate that late Quaternary geological and climatic events played a strong role in structuring northern biotic communities.

Phylogeography of lemmings ( Lemmus ): no evidence for postglacial colonization of Arctic from the Beringian refugium - V. B. Fedorov; A. V. Goropashnaya; M. Jaarola; J. A. Cook (Molecular Ecology, 2003)
Beringia is considered as an important glacial refugium that served as the main source for colonization of formerly glaciated Arctic regions. To obtain high resolution views of Arctic refugial history, we examined mitochondrial cytochrome b phylogeography in the northern genus of rodents, Lemmus ( true lemmings), sampled across its circumpolar distribution. Strong phylogeographical structure suggests vicariant separation over several glacial–interglacial periods and does not provide evidence supporting the importance of Beringia for extensive colonization of formerly glaciated regions. Rather than a source of postglacial colonization, Beringia represents an area of intraspecific endemism previously undetected by biogeographical analysis. Existing phylogeographical structure suggests that vicariant separation by glacial barriers was an important factor generating genetic divergence and, thus, increasing genetic diversity in lemmings on continental and circumpolar scales. However, there is little evidence for the direct effect of the last glaciation on the level of genetic variation and allele genealogy in lemmings on a regional geographical scale. This finding implies that the population genetic models of postglacial colonization suggested for temperate taxa might have limited applicability for Arctic species.

Colonization of an island volcano, Long Island, Papua New Guinea, and an emergent island, Motmot, in its caldera lake. VII. Overview and discussion - I. W. B. Thornton; S. Cook; J. S. Edwards; R. D. Harrison; C. Schipper; M. Shanahan; R. Singadan; R. Yamuna (Journal of Biogeography, 2001)
Location, aims Long Island's biota was destroyed by volcanic eruption in c. 1645, and Motmot, an emergent island in its caldera lake, was re‐created in 1968, providing a nested pair of natural colonization sequences. In 1999 we surveyed the plants and vertebrates of Long and the entire biota of Motmot for comparison with previous surveys of Long (1932, 1972, birds only) and Motmot (1969–88). Results The known flora of Long is 305 vascular plants (thirty‐two pteridophytes, 273 spermatophytes), including thirty‐one Ficus species, the sixteen fruiting all having pollinating wasps, and there were eleven species of effective fig dispersers. There were two frog species, a crocodile, a monitor, seven skinks, four geckos, a boid snake, fifty species non‐migrant land birds, seven bats, two rats, a cuscus (probably introduced) and feral pigs, dogs, cats and chickens. Most of Motmot's surface was barren or sparsely vegetated ash, cinder and lava fields. There were seven pteridophyte and thirty‐eight spermatophyte species, including eight Ficus , and the cumulative known flora comprises eleven pteridophytes and fifty‐one spermatophytes, mainly zoochorous and anemochorous, with sedges, grasses and herbs predominating. All Ficus individuals but one were small; three plants of two species bore syconia but had not been pollinated and had not set seed. Motmot's known invertebrate fauna comprises thirty‐five species, mainly predators and scavengers; two spider and one ant species dominating. An insectivorous bat and eight land bird species (three breeding) were the only vertebrates. Main conclusions Long's biota comprised mainly widely distributed species with broad ecological tolerances, well‐adapted for colonizing species‐poor islands. The mid‐level caldera plateau, as in 1932, was covered in fairly open forest of similar‐sized trees with a few much larger individuals and little or no understorey. Primary rain forest tree species from the region were under‐represented or absent but secondary forest species were common. There were few regional endemic Ficus species. The avifauna comprised species with good dispersal ability, lacked endemic subspecies and probably for at least the past seven decades has been held at a quasi‐equilibrium of fifty species, fourteen below the theoretical number. More than half the fifty‐four resident land birds known from Long (and three of the seven bats) are high class tramps in the sense of Diamond; only two birds are high‐S species. Turnover has been low and none of the bird super tramps has been replaced. The non‐avian fauna comprised mostly high‐category tramptype species with relatively broad habitat requirements and extensive geographical ranges. Non‐volant vertebrates comprised a number of highly vagile species associated with humans. Several groups, especially snakes and amphibians, were depauperate compared with the fauna of other islands in the area. Long's biota is evidently held at an arrested stage of development by some physical factor, possibly the extremely porous substratum and relatively dry climate. The allochthonous input of lake insects to Motmot evidently provides the major energy source for its animal communities, with a very minor contribution from organic flotsam. Reflecting Motmot's very isolated situation, plant colonization has been slow, but when more fig individuals mature and fig–wasp populations become established fruit production should attract frugivores and start a positive feedback process which will accelerate the growth of Motmot's community. Long's colonization shows similarities with that of Krakatau (Sunda Strait, Indonesia) after the 1883 eruption, and species shared by the two include a high proportion of pioneer species. Motmot's triple isolation (sea, land and fresh‐water barriers) means that its colonization differs markedly from those on two marine emergent islands of the region, Tuluman (Admiralty Group) and Anak Krakatau.

Colonization of an island volcano, Long Island, Papua New Guinea, and an emergent island, Motmot, in its caldera lake. VII. Overview and discussion - I. W. B. Thornton; S. Cook; J. S. Edwards; R. D. Harrison; C. Schipper; M. Shanahan; R. Singadan; R. Yamuna (Journal of Biogeography, 2001)

Identification and Characterization of Segments 3 and 4 of the ISAV Genome - Rachael J. Ritchie; Joël Heppell; Marcia B. Cook; Simon Jones; Steve G. Griffiths (Virus Genes, 2001)

Hepatitis E virus infection in chimpanzees: a retrospective analysis - K. A. McCaustland; K. Krawczynski; J. W. Ebert; M. S. Balayan; A. G. Andjaparidze; J. E. Spelbring; E. H. Cook; C. Humphrey; P. O. Yarbough; M. O. Favorov; D. Carson; D. W. Bradley; et al. (Archives of Virology, 2000)

Trans-Tasman Sea climate variability since ad 1740 inferred from middle to high latitude tree-ring data - R. D'Arrigo; E. Cook; R. Villalba; B. Buckley; J. Salinger; J. Palmer; K. Allen (Climate Dynamics, 2000)

Warm-season temperatures since 1600 BC reconstructed from Tasmanian tree rings and their relationship to large-scale sea surface temperature anomalies - E. R. Cook; B. M. Buckley; R. D. D'Arrigo; M. J. Peterson (Climate Dynamics, 2000)

Growth, loss, and vertical distribution of Pinus radiata fine roots growing at ambient and elevated CO 2 concentration - Stephen M. Thomas; David Whitehead; JefF. B. Reid; Freeman J. Cook; JohN. A. Adams; AlaN. C. Leckie (Global Change Biology, 1999)
Increased below‐ground carbon allocation in forest ecosystems is a likely consequence of rising atmospheric CO 2 concentration. If this results in changes to fine root growth, turnover and distribution long‐term soil carbon cycling and storage could be altered. Bi‐weekly measurements were made to determine the dynamics and distribution of fine roots ( Pinus radiata trees growing at ambient (350 μmol mol –1 ) and elevated (650 μmol mol –1 ) CO 2 concentration in large open‐top chambers. Measurements were made using minirhizotrons installed horizontally at depths of 0.1, 0.3, 0.5 and 0.9 m. During the first year, at a depth of 0.3 m, the increase in relative growth rate of roots occurred 6 weeks earlier in the elevated CO 2 treatment and the maximum rate was reached 10 weeks earlier than for trees in the ambient treatment. After 2 years, cumulative fine root growth ( P t ) was 36% greater for trees growing at elevated CO 2 than at ambient CO 2 concentration, although this difference was not significant. A model of root growth driven by daily soil temperature accounted for between 43 and 99% of root growth variability. Total root loss ( L t ) was 9% in the ambient and 14% in the elevated CO 2 treatment, although this difference was not significant. Root loss was greatest at 0.3 m. In the first year, 62% of fine roots grown between mid‐summer and late‐autumn disappeared within a year in the elevated CO 2 treatment, but only 18% in the ambient CO 2 treatment ( P L t to time accounted for between 74 and 99% of the variability. Root cohort half‐lives were 951 d for the ambient and 333 d for the elevated treatment. Root length density decreased exponentially with depth in both treatments, but relatively more fine roots grown in the elevated CO 2 treatment tended to occur deeper in the soil profile.

Abstracts of papers presented at an international workshop on management of soilborne pathogens sponsored by the United States-Israel binational agricultural research and development fund (bard) - R. J. Cook; J. Katan; I. Chet; J. Katan; R. Rodriguez-Kabana; C. R. Taylor; J. W. Kloepper; M. M. Satour; G. L. Lazarovits; K. L. Conn; M. Tenuta; G. Kritzman; et al. (Phytoparasitica, 1998)

Comparison of Ceralure and Trimedlure Controlled-Release Formulations for Male Mediterranean Fruit Flies in C&C Traps - J. D. Warthen; R. T. Cunningham; B. A. Leonhardt; J. M. Cook; J. W. Avery; E. M. Harte (Journal of Chemical Ecology, 1998)

Tree-ring records from New Zealand: long-term context for recent warming trend - R. D. D'Arrigo; E. R. Cook; M. J. Salinger; J. Palmer; P. J. Krusic; B. M. Buckley; R. Villalba (Climate Dynamics, 1998)

A CHANGING TEMPERATURE RESPONSE WITH ELEVATION FOR LAGAROSTROBOS FRANKLINII IN TASMANIA, AUSTRALIA - B. M. BUCKLEY; E. R. COOK; M. J. PETERSON; M. BARBETTI (Climatic Change, 1997)

Improved Controlled-Release Formulations for a New Trap Design for Male Mediterranean Fruit Flies: The C&C Trap - J. D. Warthen; R. T. Cunningham; B. A. Leonhardt; J. M. Cook; J. W. Avery; E. M. Harte (Journal of Chemical Ecology, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Effect of in ovo bursectomy on the course of an infectious bronchitis virus infection in line C White Leghorn chickens - J. K. A. Cook; T. F. Davison; M. B. Huggins; P. McLaughlan (Archives of Virology, 1991)

Aromatic metabolism in the fungi. Growth of Rhodotorula mucilaginosa in p-hydroxybenzoate-limited chemostats and the effect of growth rate on the synthesis of enzymes of the 3-oxoadipate pathway - Timothy J. Huber; John R. Street; Alan T. Bull; Keith A. Cook; Ronald B. Cain (Archives of Microbiology, 1975)

Sectional notes - W. B. Ward; Allan Purdy; Marx Koeiinke; H. J. Evans; Harrold Mattson; E. B. Tussing; Harold T. Cook; M. R. Harris; R. E. Goodwin; W. N. Keenan (American Journal of Potato Research, 1947)

Sectional notes - Frank E. Garrett; Roy M. Barnes; W. Frank McGee; A. H. Eddins; W. B. Ward; Verne C. Beverly; H. A. Reiley; Allan W. Purdy; J. C. Campbell; H. J. Evans; Harold Mattson; O. D. Burke; et al. (American Journal of Potato Research, 1947)